Fibro-osseous lesions of the jaws - Minić Arsa J. (Serbian Medical Society - Dental Section, Belgrade, 2003)
Fibro-osseous lesions of the jaws usually present a diagnostic dilemma for the clinician as well as the pathologist. This group includes fibrous dysplasia, ossifying fibroma, focal cemento-osseous dysplasia, periapical cemento-osseous dysplasia, and florid cemento-osseous dysplasia. As in other sites, appropriate clinicopathologic correlations are needed to reach a definitive diagnosis. The clinical and pathologic features of fibro-osseous lesions of the jaws are considered, including adequate therapeutic strategies.